2015
DOI: 10.1088/0004-637x/810/2/107
|View full text |Cite
|
Sign up to set email alerts
|

A HIGH-RESOLUTIONHUBBLE SPACE TELESCOPESTUDY OF APPARENT LYMAN CONTINUUM LEAKERS ATz∼ 3

Abstract: We present U 336 V 606 J 125 H 160 follow-up Hubble Space Telescope (HST) observations of 16 z ∼ 3 candidate Lyman continuum (LyC) emitters in the HS1549+1919 field. With these data, we obtain high spatial-resolution photometric redshifts of all sub-arcsecond components of the LyC candidates in order to eliminate foreground contamination and identify robust candidates for leaking LyC emission. Of the 16 candidates, we find one object with a robust LyC detection that is not due to foreground contamination. This… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
158
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 111 publications
(171 citation statements)
references
References 82 publications
10
158
1
Order By: Relevance
“…The new upper limit by these observations is f rel esc ∼ 7−9%, consistent with the limits by Vanzella et al (2010b) and Boutsia et al (2011). In addition, Mostardi et al (2015) reported an HST follow-up analysis of 16 candidate LyC emitters found by Mostardi et al (2013). These authors obtained deep U 336 , V 606 , J 125 , and H 160 imaging with WFC3 and ACS for these galaxies: thanks to the high spatial resolution of HST, they showed that 15 emitters can be explained by contamination of low-z objects, wrong spectroscopic redshifts, or uncertain photometric redshifts.…”
Section: Introductionsupporting
confidence: 86%
See 3 more Smart Citations
“…The new upper limit by these observations is f rel esc ∼ 7−9%, consistent with the limits by Vanzella et al (2010b) and Boutsia et al (2011). In addition, Mostardi et al (2015) reported an HST follow-up analysis of 16 candidate LyC emitters found by Mostardi et al (2013). These authors obtained deep U 336 , V 606 , J 125 , and H 160 imaging with WFC3 and ACS for these galaxies: thanks to the high spatial resolution of HST, they showed that 15 emitters can be explained by contamination of low-z objects, wrong spectroscopic redshifts, or uncertain photometric redshifts.…”
Section: Introductionsupporting
confidence: 86%
“…Imposing the constraint of a physical value for the relative escape fraction of f rel esc < 100%, the LoS of MD5b must be very transparent, exp(−τ IGM ) > 0.75, which corresponds to a probability <10 −4 , according to Inoue et al (2014). This could be an indication that this galaxy is also a low-z contaminant, similar to the other cases studied by Mostardi et al (2015).…”
Section: Comparison With Other Resultsmentioning
confidence: 80%
See 2 more Smart Citations
“…We allow fesc to vary between 0.01 and 1. Observations of star-forming galaxies at z ∼ 1-3 suggest a small average ionizing escape fraction from a few percent to smaller than 15%, which is likely to increase towards fainter galaxies (or equivalently towards higher redshifts, e.g., Iwata et al 2009;Siana et al 2010;Nestor et al 2013;Mostardi et al 2015). In recognition of the redshift dependence of Mmin, we model its variation by rescaling Mmin(z) as given by Okamoto et al (2008) by a factor of 0.1-10.…”
Section: Joint Analysis Of Galaxy Populations and The Reionization Obmentioning
confidence: 99%